iMulch: an investigation of the influence of polymers on a terrestrial ecosystem using the example of mulch films used in agriculture - Carmen Wolf; Mike Wenzel; Björn Fischer; Ralf Bertling; Erich Jelen; Dieter Hennecke; Karlheinz Weinfurtner; Martina Roß-Nickoll; Henner Hollert; Antonia Weltmeyer; Kristina Bitter; Pauline Ruiz; et al. (Environmental Sciences Europe)
Abstract Background This article provides an overview of the iMulch joint project, which analysed the use of polyethylene (PE) and biodegradable mulch films made of a polylactide (PLA) and polybutylene adipate terephthalate (PBAT) on agricultural land as a source of microplastic. The development of a detection methodology using Raman spectroscopy and thermo-extraction desorption gas chromatography mass–spectrometry (TED-GC–MS), the adsorption behaviour, ageing in drainage water and soil, their transport behaviour in lysimeters, ecotoxicity, uptake in plants, a life cycle assessment (LCA) and upcycling were considered. Results The PE film tested showed hardly any degradation or fragmentation during the ageing tests. The biodegradable films showed incipient degradation after 8 weeks in drainage water and initial degradation after 12 weeks in soil ageing experiments. Additionally no degradation could be detected in the lysimeter test within the 24 months analysed. The biodegradable films could be metabolized in laboratory tests with some microorganisms present in the soil. This indicates that these films can be degraded in the environment if the conditions for degradation are optimal. No microorganisms or fungi that could degrade the PE film within a respective period of time were detected in the soil. Adsorption of the tested substances was not observed. Incorporated in soil, mulch film microplastic showed retention of extractable pesticides. In the ecotoxicological tests, both film types showed no acute toxic effects in the earthworm Eisenia fetida and the springtail Folsomia candida. Endocrine activity was observed in eluate samples from both films. However, aged films showed fewer effects than non-aged films. Conclusion Both types of film show no transport or degradation in the tests under real conditions, which means that they remain in the upper soil layer, where they are available to soil organisms and can lead to high concentrations in the future. As the biodegradable film could be degraded, at least under ideal conditions, we recommend its use. However, proof of degradation must first be verified under real field conditions. In addition, we recommend the use of thicker conventional mulch films to minimize the emission of plastic particles. For this purpose, a minimum lower limit for the material thickness should be defined. Graphical Abstract